Respuesta :
x-4y-1=0
-x-5y-4=0
----------------
0+y+3=0
y+3-3=0-3
y=-3
Substituting y=-3 in the equation x-4y-1=0
x-4×-3-1=0
x+12-1=0
x+11-11=0-11
x=-11
-x-5y-4=0
----------------
0+y+3=0
y+3-3=0-3
y=-3
Substituting y=-3 in the equation x-4y-1=0
x-4×-3-1=0
x+12-1=0
x+11-11=0-11
x=-11
Answer:
(x,y) = (7/3,1/3)
Step-by-step explanation:
x - 4y - 1 = 0 ------ Equation 1
x + 5y - 4 = 0 ------ Equation 2
From equation 1,
x = 4y + 1 (substitute into equation 2)
4y + 1 + 5y - 4 = 0
9y = 3
y = 1/3
Substitute into x = 4y + 1
x = 4(1/3) + 1
x = 4/3 + 1
x = 7/3
Therefore,
(x,y) = (7/3,1/3)